Integrated use of cultivation practices increases the Tartary buckwheat yield by improving the photosynthetic capacity and nitrogen utilization rate - Dai, Lihua; Yang, Qiong; Cai, Fang; Tang, Jingang; Huang, Kaifeng (Frontiers in Plant Science, 2025)
IntroductionYield improvement of Tartary buckwheat is primarily hindered by the lack of effective cultivation practices. Understanding the effects of improved cultivation practices (ICPs) on the yield and economic benefits is of great importance for high-yield cultivation and resources efficient utilization of Tartary buckwheat.MethodsA two-season field experiment was conducted on Tartary buckwheat variety Jinqiao 2 using six cultivation practices, including no nitrogen application (0 N), local farmers’ practice (LFP, CK), and four ICPs consisting of improved practice of increased planting density with reduced nitrogen application (ICP1), the same practices as ICP1 but with moderate tillage depth (ICP2), the same practices as ICP1 but with deep tillage depth (ICP3), and the same practices as ICP3 but with rice straw returning (ICP4).Results and discussionICP4 treatment remarkably increased the chlorophyll content, photosynthetic rate, photosynthetic nitrogen utilization efficiency, non-structural carbohydrate accumulation, transportation, contribution rate to grain yield, physiological utilization rate of nitrogen fertilizer, agronomic utilization rate of nitrogen fertilizer, and partial productivity of nitrogen fertilizer. Compared with LFP treatment, ICP1, ICP2, ICP3, and ICP4 treatments increased the yield of Tartary buckwheat by 15.63%, 32.03%, 46.09%, and 79.69%, respectively. ICP4 treatment was the best among the cultivation practices, but considering the cost (Compared with LFP, ICP3 increased the production value, economic output–input ratio, and cost–output rate by 45.99%, 47.97%, and 64.45%, respectively), the use of ICP3 was favorable in the production of Tartary buckwheat. This study was helpful in establishing integrated agronomic practices for high-yield cultivation and resources efficient utilization for the Tartary buckwheat production.